The Role of Pancasila Education Course in Shaping Religious Diversity Tolerance Attitudes in FPBS UPI Environment - Farha, Nathan Syidda; Alfarizy, Muhammad Rizky; Syafitri, Intan Mariam; Huriyah, Reva Fidela; Nabila, Yasmin Azzahra Rava; Supriyono, Supriyono (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study examines the role of the Pancasila Education course in shaping students' tolerance toward religious diversity at the Faculty of Language and Arts Education (FPBS), Universitas Pendidikan Indonesia, using a descriptive qualitative approach. Seven students served as research subjects, with data collected through observation and structured interviews, then analyzed following the Miles and Huberman model — encompassing data collection, reduction, categorization, and conclusion drawing. All seven respondents agreed that the course carries a measurable positive effect on inter-student tolerance, particularly in how students treat peers from different religious backgrounds. By centering on moral conduct and civic values, the course gives students a working understanding of humanist and nationalist principles that they carry into daily campus life — reflected in attitudes of mutual respect and the absence of discriminatory behavior across religious groups. The course succeeds not by preaching unity in the abstract, but by pushing students to translate the values of solidarity, humanity, and social justice into concrete behavior, ultimately producing a campus culture where religious coexistence is not merely tolerated, but actively maintained.